Anion directed cation templated synthesis of three ternary copper(II) complexes with a monocondensed N2O donor Schiff base and different pseudohalides. (8th January 2015) - Bhowmik, Prasanta; Bhattacharyya, Anik; Harms, Klaus; Sproules, Stephen; Chattopadhyay, Shouvik
Abstract : Graphical abstract: A tridentate monocondensed N2 O donor Schiff base ligand has been trapped in three different copper(II) complexes. X-ray diffraction studies have confirmed the structures of the complexes. The formation of the complexes have been explained by the concept of anion directed cation templated synthesis. Variable temperature magnetic measurements indicate antiferromagnetic interactions between the copper(II) centers in all three complexes. Abstract: Three copper(II) complexes, [Cu2 (L)2 (μ1, 1 -N3 )2 ] (1 ), [Cu2 (L)2 (μ1, 1 -NCO)2 ] (2 ) and [Cu(L)(μ1, 5 -dca)] n (3 ), where HL is a tridentate mono-condensed Schiff base, 1-(2-aminoethyliminomethyl)naphthalen-2-ol, and dca is dicyanamide, have been prepared and characterized by elemental analysis, IR, UV–Vis and fluorescence spectroscopy and single crystal X-ray diffraction studies. The Schiff base ligand was prepared by a counter anion mediated copper(II) templated synthesis. The azide ligand in complex1 and the cyanate ligand in complex2 show μ-1, 1 bridging modes, whereas the dca ligand shows the μ-1, 5 bridging mode in complex3 . Three equatorial positions of copper(II) are occupied by the tridentate Schiff bases in all three complexes. The fourth equatorial sites are occupied by nitrogen atoms of azide in1, cyanate in2 and dca in3 . Another nitrogen atom from a symmetry related pseudohalide coordinates in the axial position of copper(II) to complete its square pyramidal geometry in each of the complexes. Significant supramolecular interactions are observed in all the complexes. Variable temperature magnetic measurements indicate antiferromagnetic interactions between the copper(II) centers in all three complexes.